Conversion of h-BN into c-BN for tuning optoelectronic properties. Issue 4 (25th June 2020) - Haque, Ariful; Narayan, Jagdish
Abstract : Phase pure c-BN and mixed phased h-BN and c-BN films on c-sapphire were fabricated by pulsed laser annealing for tuning optical properties. Abstract : Boron nitride (BN) films containing different percentages of cubic phase contents were grown on a (0001) sapphire substrate using a novel pulsed laser processing method. To synthesize cubic boron nitride (c-BN), the hexagonal boron nitride (h-BN) target was ablated by a pulsed KrF laser ( λ = 248 nm) during the pulsed laser deposition process followed by the pulsed laser annealing (PLA) with an ArF laser ( λ = 193 nm). We performed a set of detailed characterization analyses on the fabricated BN films by Raman spectroscopy, X-ray diffraction (XRD), high resolution SEM, EBSD, and UV-Vis measurements. Raman spectroscopy was successfully utilized to identify the crystalline quality and to determine the fraction of c-BN phase quantitatively in the BN films. Here, we report that c-BN phase content can be tuned by the laser energy density during the PLA treatment. The optical bandgap of the fabricated BN films was found to increase with increasing cubic phase content and a correlation was obtained between the optical bandgap and the c-BN phase content in the films. The details of the structure–property correlation and the possible applications of these films are discussed.